Toll-like receptor 2 and 4 genes influence susceptibility to adverse effects of traffic-related air pollution on childhood asthma. Issue 8 (4th August 2010) - Kerkhof, M; Postma, D S; Brunekreef, B; Reijmerink, N E; Wijga, A H; de Jongste, J C; Gehring, U; Koppelman, G H
Abstract : Background: Epidemiological studies have reported adverse effects of ambient air pollution on the prevalence of asthma. Laboratory studies have suggested that innate immune responses are involved. Objective: A study was undertaken to determine whether the Toll-like receptor 2 and 4 genes ( TLR2 and TLR4 ) influence the susceptibility to adverse effects of traffic-related air pollution with respect to the prevalence of childhood asthma. Methods: Haplotype tagging single nucleotide polymorphisms (SNPs) in the TLR2 (n=4) and TLR4 genes (n=9) were genotyped in 916 children from the Prevention and Incidence of Asthma and Mite Allergy (PIAMA) birth cohort. Exposure to particulate matter (PM2.5 ), soot and nitrogen dioxide (NO2 ) at the birth address was estimated by land use regression models. Interactions between levels of pollutants and SNPs in relation to annual questionnaire reports of asthma diagnosis and symptoms from birth up to 8 years of age were analysed longitudinally by generalised estimating equations. Results: Two TLR2 SNPs and four TLR4 SNPs significantly modified the effect of air pollution on the prevalence of doctor-diagnosed asthma from birth up to 8 years of age. The risk of having doctor-diagnosed asthma increased with increasing PM2.5 levels in children with at least one copy of the TLR2 rs4696480 A allele (OR 2.0 (95% CI 1.2 to 3.1) for an interquartile range increase in exposure). Similar observations were present with the following TLR4 genotypes: rs2770150 TC (OR 2.0 (95% CI 1.1 to 3.6)), rs10759931 GG (OR 2.6 (95% CI 1.4 to 4.9)), rs6478317 GG (OR 2.2 (95% CI 1.2 to 4.3)), rs10759932 CT or CC (OR 2.9 (95% CI 1.2 to 6.9)) and rs1927911 TT (OR 4.4 (95% CI 1.7 to 11.7)). Conclusions: Variant alleles of TLR2 and TLR4 genes influence the susceptibility to adverse effects of traffic-related air pollution on childhood asthma.